Advokasi Transportasi Berkelanjutan melalui Pembelajaran Moda di Jepang pada Festival Bunkasai Universitas Syiah Kuala, Banda Aceh - Caisarina, Irin; Mufiaty, Hilda; Taqiuddin, Zulfikar; Fakhrana, Siti Zahrina (Universitas Syiah Kuala, 2025)
This community service aims to promote public awareness of sustainable transportation through learning from Japans multimodal transport system. The activity was held at the Bunkasai Festival of Syiah Kuala University in Banda Aceh, where visitors were introduced to Japans transportation modesranging from rail, bus, bicycle-sharing, and walking systemsthrough maps, models, and interactive discussions. The program also presented a case study on the potential for Transit-Oriented Development (TOD) along Banda Acehs Trans Koetaradja corridor, connecting the concept of sustainability in transport with local practices. This initiative adopted an informative exhibition method supported by visual aids such as transport maps, infographics of Japanese mobility systems, and an audio visual content showing how transportation system works Japan. The main objectives were to enhance community knowledge about sustainable transport, encourage discussions about alternative modes to private motorized vehicles, and introduce the relevance of TOD principles for Banda Acehs urban mobility. The results show that most visitors demonstrated increased awareness and curiosity about sustainable modes after engaging with the exhibition. The activity highlights the potential for public education and advocacy through cultural festivals as a means of linking academic research, urban sustainability, and community participation.